The First Experience of Laparoscopic Gastroepiploic Artery Harvesting during Complete Autoarterial Myocardial Revascularization - A. Gabriyelyan; A. Sidyuk; A. Mazur; T. Domanskyy; O. Beregovoy; V. Beleiovych; A. Mironyuk; S. Romanova; I. Kudlai; I. Havin; G. Savenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
The use of autoarterial grafts for myocardial revascularization is a priority for cardiac surgery. Laparoscopic right gastroepiploic artery (RGEA) harvesting may significantly reduce the risks of complications associated with laparotomy and expand the possibilities of its use as an autoarterial graft during coronary artery bypass grafting.The aim. To represent the first experience of using the laparoscopically harvested RGEA as a graft for full autoarterial bypass surgery.Materials and methods. Five coronary artery bypass surgeries using autoarterial grafts – two internal thoracic and one right gastroepiploic arteries – were performed on a beating heart. All the patients were males at the average age of 51 ± 8 had multifocal coronary artery damage. In all cases, RGEA was harvested laparoscopically.Results. In the early postoperative period, patients did not have any cardiovascular events such as perioperative myocardial infarction, acute cerebrovascular accident, or arrhythmia. There were no gastrointestinal complications such as gastrostasis, stool disorders, vomiting. No significant differences were found between the indicators in patients who underwent complete autoarterial revascularization using RGEA and those who underwent surgery using the traditional method (LIMA-LAD, other arteries are bypassed by the veins).Medium-term results of observation show the absence of angina pectoris and complications associated with the use of RGEA.Conclusions. The first experience of using laparoscopically isolated RGEA as an arterial conduit for the coronary arteries bypassing showed positive results. The use of modern laparoscopic techniques allows for safer and less traumatic harvesting of RGEA.